RINTISAN GREEN ECONOMY MELALUI PLTMH DI KRAJAN, CANGKRINGAN, SLEMAN - Novianta, Muhammad Andang; Iswahyudi, Catur (LPPM IST AKPRIND Yogyakarta, 2023)
Krajan is located about 20 km from the summit of Mount Merapi. The main problem in this village is the Community-based Drinking Water and Sanitation Program (PAMSIMAS) which has played a role in meeting the community's clean water needs, but has not been able to be used economically by the residents despite having abundant mountain springs. In addition, water problems arise especially during the rainy season, where water does not meet quality standards so it is not suitable for consumption. To optimize the use of springs that have an impact on green economy activities as well as improve people's welfare, the PKM Team of the IST AKPRIND Yogyakarta applies a (PLTMH) in Padukuhan Salam-Krajan, Wukirsari, Cangkringan. PLTMH was developed by utilizing abundant springs. By utilizing the water discharge from the water input (inlet) flow to the PAMSIMAS reservoir, the electricity generated can be used for street lighting as well as building ready-to-drink water installations using the electricity network from PLTMH. Based on the evaluation of the activity, the implementation of community service activities that harmonize the needs of partners with the competence of the Team is a very good model for implementing community service activities, so this kind of model needs to be continued. This PKM activity is able to provide opportunities to support the implementation of development that is oriented towards environmental and ecosystem aspects, able to improve the welfare of rural communities, plan sustainable development, a green economy, overcome poverty and produce ready-to-drink water products.